Immigration and Worker-Firm Matching - Orefice, Gianluca; Peri, Giovanni (The Review of Economics and Statistics, 2024)
Abstract Positive assortative matching increases both the wages of more productive workers and wage dispersion. We study the effect of immigration on positive assortative matching using French employer-employee data from 1995 to 2005. We find that increases in the share of immigrants, driven by historical networks across local labor markets, generated stronger positive assortative matching between workers and firms. We present evidence suggesting that this effect was associated to higher wages for more productive workers and that the findings are consistent with increased workers' screening by firms.